Integrating Strategic Planning and Academic Standards in Higher Education: Insights from a Digitalpreneurship Program Case Study - Arinindyah, Otisia; Nurhayati, Wakhida; Shofiyullah, Shofiyullah; Zawirrahmi, Zawirrahmi; Sulastini, Rita (International Journal of Social and Management Studies, 2025)
In response to the growing importance of digital entrepreneurship in the global economy, higher education institutions are increasingly tasked with designing programs that equip students with the competencies needed to navigate and lead in digital environments. This study investigates how Universitas Insan Pembangunan Indonesia (UNIPI), a private university in Indonesia, strategically plans and standardizes its academic offerings to develop a sustainable digitalpreneurship program. Employing a descriptive qualitative approach, data were collected through document analysis, in-depth interviews with institutional leaders, program chairs, lecturers, and students, as well as direct classroom observations. Thematic analysis revealed five major themes: strategic vision and institutional positioning, curriculum alignment with national standards (SN-Dikti and KKNI), quality assurance mechanisms, implementation challenges and pedagogical practices, and stakeholder engagement. Findings indicate that while UNIPI has articulated a strong institutional vision for digital entrepreneurship, operational implementation remains uneven across departments due to variations in faculty readiness, infrastructural access, and industry collaboration. Curriculum design shows compliance with national education standards, but gaps exist in translating such standards into innovative teaching practices. Students generally value experiential learning opportunities but express a need for stronger mentoring, startup incubation support, and practical engagement. This study contributes to the literature by offering a contextualized model of how private universities in emerging economies can integrate strategic planning and academic standardization to foster digitalpreneurship. It highlights the critical need for institutional reflexivity, coordinated leadership, and adaptive governance to build a sustainable and inclusive digital entrepreneurial ecosystem in higher education.